Piotórax crônico em cão por vagem de Acácia Imperial (Cassia fistula) - de Abreu, Claudine Botelho; Coelho, Lívia de Paula; Nogueira, Rodrigo Bernardes; Salgueiro, Nathália Brant Malta; Lacreta Junior, Antônio Carlos Cunha; Irino, Eduardo Toshiro; de Oliveira, Luiz Eduarte Duarte (Acta Scientiae Veterinariae, 2017)
Background: Pyothorax is characterized by the accumulation of septic purulent fluid within the pleural space. Most of the times, it is the true identified infection way in only 2 to 22% of dog cases. Reports show that the most common cause is the migration of grass edges and plant materials, mainly in regions of California, USA. The current study reports an unusual case of a Cassia fistula pod (Brazilian Acácia Imperial), of around 10x3 cm long, causing chronic Pyothorax in a Border Collie female dog. Case: It was admitted in a Teaching Veterinary Hospital a 2-year-old female Border Collie, weighing 16.5 kg. The complaint was producing of severe cough, dyspnoea, hyporexia and loss of weight in the past three months. The animal could have been horse-kicked, as it is used to herding. In the physical examination, it was detected bilateral thick lung crepitations, more evident in the ventral skull area, dyspnoea, tachypnea, fever, splenomegaly and low body condition score (3/9). The laboratory tests revealed nonregenerative anemia and leukemoid reaction. The chest x-ray showed intense pulmonary opacification and free fluids in the pleural space along with a heterogenic cylindrical image of the mixed radiopacity. This image was then confirmed as the intrathoracic foreing body by the use of a computerized tomography. In this exam it was also possible to observe the damage of part of the middle and inferior right lung lobe. The cytology of the pleural effusion found mixed inflammation and coccoid bacteria, and the microbiological culture Streptococcus sp., and Escherichia coli. The dog underwent thoracotomy in order to remove the foreign body, which was later identified as being a Cassia fistula pod (Brazilian Acácia Imperial), of around 10x3 cm long. Due to the intense lung damage, a right pneumonectomy was required. After 30 days the animal was fully recovered. Discussion: The applied surgical procedure ended up being the most correct, due to the shape and place of the foreign body, and also due to the massive damage of the lobes on the right lung. In dogs, right pneumonectomy may cause respiratory acidosis and exercise intolerance, besides it can also show signs of hyperinflation in some pulmonary spots. However, such abnormalities were not perceived by the patient. There are a few reports concerning the right pneumonectomy applicability on veterinary routine, nevertheless, it is a perfect practicable intervention from the clinic-surgical perspective, according to this case’s reports. Initially, the possibility of a foreign body was not expected, once the history of a plausible trauma, caused by horse-kick, associated to the presence of thoracic effusion, influenced only to the Pyothorax’s etiology. But the continuity of the clinic condition and the cylindrical image in subsequent x-rays favored the suspect of an foreign body, which could be confirmed in the computerized tomography. However, the way the pod got into the animal’s thorax, adhering to the lung parenchyma, remained undetermined. Besides, there were not found clinic descriptions relating the Cassia fistula pod (Brazilian Acácia Imperial) as an etiological agent of intra-thoracic foreign body in dogs, making this report an unusual clinic case. The computerized tomography was primordial to the definite diagnostic and for choosing the type of surgical procedure to be applied. The right pneumonectomy associated to the removal of the foreign body promoted the success of the treatment without further post-operatory complications.